Bioactivity-Guided Isolation of Cytotoxic and Antioxidant Phytochemicals from Four Cousinia Species from Stenocephala Bunge Section - Pasayeva, Leyla; Ustun, Osman; Demirpolat, Eren; Karatoprak, Gokce S.; Tugay, Osman; Kosar, Muberra (Wolters Kluwer Medknow Publications, 2019)
Background: Asteraceae family contains several cytotoxic compounds bearing genus. Cousinia genus is included in the Asteraceae; it has not been studied phytochemically in detail. Objective: In this study, chemical compositions of four Cousinia species (Cousinia davisiana [CD], Cousinia foliosa, Cousinia ramosissima, and Cousinia stenocephala [CS]) were evaluated according to their cytotoxic and antioxidant effects using bioactivity-guided isolation. Materials and Methods: The cytotoxic effect was investigated with Sulphorhodamine B method against Colo205 (human colon carcinoma), A549 (human non- small cell lung cancer) cell lines, and antioxidant activity tested with 1,1-diphenyl-2-picrylhydrazyl, 2,2' azino-bis 3-ethylbenzothiazoline-6-sulphonic acid scavenging tests, and beta-carotene/linoleic acid co-oxidation test. Purified compounds were elucidated by one-dimensional and two-dimensional nuclear magnetic resonance and mass spectroscopic techniques. The quantitative and qualitative determination of unpurified compounds within the extracts was carried out by liquid chromatography-mass spectrometry/mass spectrometry. Results: CS methanol extract, dichloromethane subextract, and FR-3 showed more cytotoxicity; isolated compound (psi-taraxasterol) showed no cytotoxic activity. CD methanol extract and n-butanol subextract showed significant antioxidant activity. Conclusion: This is the first report that these phytochemical compounds were identified in Cousinia genus, and it is thought that these compounds could contribute to the chemotaxonomy of the genus.
Keywords: Antioxidant; Cousinia; cytotoxicity; liquid chromatography-mass spectrometry/mass spectrometry; nuclear magnetic resonance